Epidural Catheter-Assisted Percutaneous Transforaminal Endoscopic Diskectomy: A Technical Note - Kim, Ki Joon; Jang, JeeSoo; Jang, Il-Tae (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background With advances in techniques and instruments, percutaneous endoscopic transforaminal lumbar diskectomy (PETLD) is now widely used for lumbar disk herniation. Although the indication for PETLD is expanding, the technique still has limitations. To overcome them, we performed the epidural catheter-assisted PETLD described here.Methods A 49-year-old woman had severe radiating pain in a left L5 dermatomal distribution. Magnetic resonance imaging (MRI) revealed left paramedial disk herniation at L4–L5 and a small downward-migrated disk fragment. We performed epidural catheter-assisted PETLD. Mechanical outward pushing and normal saline injection through the epidural catheter were performed for removal of hidden disk remnants. In the second case, a 26-year-old man presented with severe radiating pain in the L5–S1 dermatoms on both sides. MRI revealed massive disk herniation at L4–L5. A unilateral approach was used, and the ruptured disk could be moved using an epidural catheter.Results The patients' pain improved immediately after the procedures. With this method, neural decompression can be performed more easily and effectively.Conclusions Epidural catheter-assisted PETLD has several advantages and can overcome the limitations of conventional PETLD.
Keywords: epidural catheter; percutaneous endoscopic transforaminal lumbar diskectomy; neural decompression; lumbar disk herniation